Congestive Heart Failure and Diabetes: Balancing Glycemic Control with Heart Failure Improvement - Nasir, Saifullah (2012)
Diabetes and congestive heart failure (HF) commonly coexist in the same patient, and the presence of diabetes in HF patients is associated with increased adverse events compared to patients without diabetes. Recent guidelines regarding glycemic control stress individualization of glycemic therapy based on patient comorbid conditions and potential adverse effects of medical therapy. This balance in glycemic control may be particularly relevant in patients with diabetes and HF. In this review, we address data regarding the influence that certain HF medications may have on glycemic control. Despite potential modest changes in glycemic control, clinical benefits of proven pharmacologic HF therapies extend to patients with diabetes and HF. In addition, we review potential benefits and challenges associated with commonly used glycemic medications in HF patients. Finally, recent data and controversies on optimal glycemic targets in HF patients are discussed. Given the large number of patients with diabetes and HF and the health burden of these conditions, much needed future work is necessary to define the optimal glycemic treatment in HF patients with diabetes.